Associations between social capital and depression: A study of adult twins - Cohen-Cline, Hannah; Beresford, Shirley AA; Barrington, Wendy; Matsueda, Ross; Wakefield, Jon; Duncan, Glen E. (Health & place, 2018)
Social capital is associated with depression independently of individual-level risk factors. We used a sample of 1586 same-sex twin pairs to test the association between seven measures of social capital and two related measures of neighborhood characteristics with depressive symptoms accounting for uncontrolled selection factors (i.e., genetics and shared environment). All measures of cognitive social capital and neighborhood characteristics were associated with less depressive symptoms in between-twin analysis. However, only measures of cognitive social capital were significantly associated with less depressive symptoms within-pairs. These results demonstrate that cognitive social capital is associated with depressive symptoms free of confounding from genetic and environmental factors shared within twins. •Social capital is associated with depression at the individual level.•Familial (genetic and shared environment) factors may confound associations.•Twins are used to test associations free of such confounds.•Cognitive social capital is associated with depression between and within-twins.•Cognitive social capital is associated with depression free of familial confounds.